Kepemimpinan Partisipatif dalam Pengembangan Lembaga Dakwah: Membangun Efektivitas, Inovasi, dan Keberlanjutan - Baharudin Ardani; Cecep Castrawijaya (Reflection : Islamic Education Journal, 2025)
Participative leadership in dakwah institutions offers clear benefits. Literature indicates this style improves decision quality and spurs innovation, as members with relevant knowledge contribute creative solutions. It fosters an inclusive culture where stakeholders feel valued, responsible, and committed to collective decisions. Organizational effectiveness and efficiency rise with increased participation and member engagement. However, full implementation encounters practical challenges. In dakwah organizations with hierarchical traditions, resistance to power-sharing and trust deficits can cause conflict and decision delays. Limited leadership capacity and communication skills among members become obstacles if leaders are untrained in participative methods. Organizational theory thus recommends adaptive strategies: leaders should establish effective communication channels, empower teams, and implement context-specific leadership training programs. Case studies suggest these measures build a sustainable collaborative culture that supports innovation in dakwah programs. In summary, participative leadership, when combined with appropriate training and a supportive culture, can enhance effectiveness, foster creativity, and ensure organizational sustainability in religious outreach.